Synthesis and Characterization of Novel Copolymeric Resveratrol Conjugates - Yan-Jing Ng; Heather A. E. Benson; David H. Brown; Yan Chen (Journal of Chemistry)
Resveratrol (RSV), naturally found in plants, is known to have health benefits and has been proposed as a potential anticancer and cardioprotective drug. However, due to its molecular structure, it undergoes rapid metabolism in the body resulting in low bioavailability. Novel polymeric methoxy-poly(ethylene glycol)-block-poly(ε-caprolactone) (mPEG-PCL) RSV conjugates with varying PCL chain lengths have been synthesised and formulated into micelles and/or nanoparticles for preliminary in vitro stability studies. RSV conjugated with mPEG2000-PCL9500 was found to have improved solubility and stability of RSV as compared to RSV alone. The length of the PCL chain was found to affect the micelle formation, hence the stability in physiological buffers and rat plasma.